2020
DOI: 10.4038/sljog.v42i3.7956
|View full text |Cite
|
Sign up to set email alerts
|

Awareness, knowledge and the factors that affect the use of folic acid among pregnant and non-pregnant women in the reproductive age in a selected area in Colombo district, Sri Lanka

Abstract: Background:The prevalence of neural tube defects in Sri Lanka is estimated to be 1.21 per 1000 births. According to the WHO, programs to increase folic acid (FA) consumption among women of reproductive age may benefit countries where the NTD rate is higher than 0.6/1,000 live births. Food fortification is an effective method but there is still no mandatory fortification policy in Sri Lanka. Therefore, improving knowledge and voluntary use of FA remains a high priority. The study aimed to determine the awarenes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
4
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 23 publications
(31 reference statements)
2
4
2
Order By: Relevance
“…Although the overall knowledge was good, knowledge on the preconception folic acid supplementation was low (47.1%) in our study when compared to a study done in Sri Lanka where 94.3% of the women were aware of preconception folic acid supplementation 22 . This could be due to the sources of information on PCC in our study where major sources were from friends, family and social media, rather than from health workers.…”
Section: Discussioncontrasting
confidence: 89%
See 1 more Smart Citation
“…Although the overall knowledge was good, knowledge on the preconception folic acid supplementation was low (47.1%) in our study when compared to a study done in Sri Lanka where 94.3% of the women were aware of preconception folic acid supplementation 22 . This could be due to the sources of information on PCC in our study where major sources were from friends, family and social media, rather than from health workers.…”
Section: Discussioncontrasting
confidence: 89%
“…In this study, only 25.3% of our participants had taken preconception folic acid supplementation which was lower than some of the studies carried out in Sri Lanka (44.9%) and China (37.9%) 19,22 . The reason for this low level of practice of preconception folic acid supplementation was that our participants had low level of knowledge on preconception folic acid usage and its benefits on reduction of congenital malformation by folic acid supplementation.…”
Section: Discussioncontrasting
confidence: 60%
“…However, previous studies conducted in different parts of the world have reported that majority of participating women had poor knowledge of the role of FA regarding prevention of NTDs (Nosrat, 2012;Alanazi et al, 2021;Begashaw et al, 2022). The same is true for Sri Lanka, where a study focusing on knowledge about preconceptual use of FA using pregnant and non-pregnant women, revealed that participants' knowledge related to preconceptual use of FA was significantly low (Pathiraja & Prathapan., 2020).…”
Section: Introductionmentioning
confidence: 96%
“…It is estimated that around 300,000 infants are born each year with NTDs, and approximately 88,000 deaths occur due to NTDs (Zaganjor et al, 2016). In Sri Lanka, the estimated prevalence of NTDs is 1.21 per 1000 births and recurrence risk of NTDs as 2%-3% (Pathiraja & Prathapan, 2020).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation